The Construction of Satan’s Weltanschauung in the Qur’an: Toshihiko Izutsu’s Semantic Approach - Nurul Husna; Irfansyah Irfansyah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2026)
For centuries, shaytan in Islamic discourse has generally been understood as a single entity with a fixed meaning, a perception inherited from classical exegetical traditions that primarily rely on atomistic verse-by-verse interpretations. Although studies employing Toshihiko Izutsu's semantic approach have expanded in Indonesia, no previous research has comprehensively analyzed shaytan using Izutsu's complete semantic framework, encompassing semantic fields, diachronic development, and the Qur'anic worldview. This study aims to examine the semantic structure of shaytan through Izutsu's semantic methodology in order to reconstruct its conceptual meaning within the Qur'an. The research adopts a qualitative hermeneutic-semantic approach, using the Qur'an as the primary source and classical Arabic lexicons, biblical texts, Israelite literature, and relevant scholarly works as supporting data. The findings demonstrate that shaytan is not merely a proper name but an existential category denoting persistent estrangement from divine truth. Synchronically, it occupies a hierarchical position within the Qur'anic semantic system as the antithesis of divine guidance, while diachronically the Qur'an reinterprets pre-Islamic and biblical traditions by introducing a distinctive ethical narrative centered on istikbar (arrogance) as the root of rebellion. These findings contribute to Qur'anic semantic studies by expanding Izutsu's framework and demonstrating that the Qur'anic weltanschauung conceptualizes shaytan as a multidimensional moral category emphasizing human responsibility, gradual psychological temptation, asymmetric dualism, and humanity's continuing capacity to resist evil.